Pre-exposure and postexposure prophylaxes and the combination HIV prevention methods (The Combine! Study): protocol for a pragmatic clinical trial at public healthcare clinics in Brazil. Issue 8 (25th August 2015) - Grangeiro, Alexandre; Couto, Márcia Thereza; Peres, Maria Fernanda; Luiz, Olinda; Zucchi, Eliana Miura; Castilho, Euclides Ayres de; Estevam, Denize Lotufo; Alencar, Rosa; Wolffenbüttel, Karina; Escuder, Maria Mercedes; Calazans, Gabriela; Ferraz, Dulce; et al.
Abstract : Introduction: Few results from programmes based on combination prevention methods are available. We propose to analyse the degree of protection provided by postexposure prophylaxis (PEP) for consensual sexual activity at healthcare clinics, its compensatory effects on sexual behaviour; and the effectiveness of combination prevention methods and pre-exposure prophylaxis (PrEP), compared with exclusively using traditional methods. Methods and analysis: A total of 3200 individuals aged 16 years or older presenting for PEP at 5 sexually transmitted disease (STD)/HIV clinics in 3 regions of Brazil will be allocated to one of two groups: the PEP group—individuals who come to the clinic within 72 h after a sexual exposure and start PEP; and the non-PEP group—individuals who come after 72 h but within 30 days of exposure and do not start PEP. Clinical follow-up will be conducted initially for 6 months and comprise educational interventions based on information and counselling for using prevention methods, including PrEP. In the second study phase, individuals who remain HIV negative will be regrouped according to the reported use of prevention methods and observed for 18 months: only traditional methods; combined methods; and PrEP. Effectiveness will be analysed according to the incidence of HIV, syphilis and hepatitis B and C and protected sexual behaviour. A structured questionnaire will be administered to participants at baseline and every 6 months thereafter. Qualitative methods will be employed to provide a comprehensive understanding of PEP-seeking behaviour, preventive choices and exposure to HIV. Ethics and dissemination: This study will be conducted in accordance with the resolution of the School of Medicine Research Ethics Commission of Universidade de São Paulo (protocol no. 251/14). The databases will be available for specific studies, after management committee approval. Findings will be presented to researchers, health managers and civil society members by means of newspapers, electronic media and scientific journals and meetings.